Exploring perspectives, uses, implications and needs of the educational e-portfolio in the arts. A systematic review of the scientific literature - Calderón-Garrido, Diego; Gil-Fernández, Raquel; Martín-Piñol, Carolina (SAGE Open, 2024)
In recent years, the emergence of digital technology and the creation of new opportunities and contexts have given rise to significant changes in the teaching and learning strategies and evaluation processes used in artistic disciplines, including use of the digital portfolio. This work consisted of a systematic analysis of the literature produced on this subject thus far in JCR, SCOPUS, and ERIC to detect practices, limitations, and opportunities. Following the analysis of the selected sample, which consisted of 32 articles, three main categories were established: development of artistic competences, teacher training and employability. The main findings related to the benefits of the digital portfolio for the development of competences, artistic identity and digital literacy through reflective practices. The study concluded that more experimental studies are needed to explore the digital portfolio and the design of more flexible and sustainable platforms, and demonstrated that there is a clear need for curricular changes to bring about improvements.
Keywords: digital portfolio; evaluation; development of competences; digital competence; reflective practices; artistic disciplines; Scopus; JCR